2010
DOI: 10.1017/s0007485310000337
|View full text |Cite
|
Sign up to set email alerts
|

PCR-based species identification ofAgrioteslarvae

Abstract: Click beetle larvae within the genus Agriotes (Coleoptera: Elateridae), commonly known as wireworms, are abundant ground-dwelling herbivores which can inflict considerable damage to field crops. In Central Europe up to 20 species, which differ in their distribution, ecology and pest status, occur in arable land. However, the identification of these larvae based on morphological characters is difficult or impossible. This hampers progress towards controlling these pests. Here, we present a polymerase chain reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 42 publications
2
42
0
Order By: Relevance
“…air entrainments, and data on their electrophysiological and behavioural activities (Tóth et al 2008), as well as the preliminary molecular comparison of the two species in the present study may suggest the taxa to which the two described morphological forms belong, represent a stage of species diversification, or may just be geographical populations or races of the same species. This may be supported by Staudacher et al (2011) who also found high similarity between the two species based on the analysis of a region of the COI gene different from that investigated in this study. To test this hypothesis, additional studies concerning the similarities/differences in other regions of the genom (e.g.…”
Section: Discussionsupporting
confidence: 83%
“…air entrainments, and data on their electrophysiological and behavioural activities (Tóth et al 2008), as well as the preliminary molecular comparison of the two species in the present study may suggest the taxa to which the two described morphological forms belong, represent a stage of species diversification, or may just be geographical populations or races of the same species. This may be supported by Staudacher et al (2011) who also found high similarity between the two species based on the analysis of a region of the COI gene different from that investigated in this study. To test this hypothesis, additional studies concerning the similarities/differences in other regions of the genom (e.g.…”
Section: Discussionsupporting
confidence: 83%
“…Agriotes proximus, also classified as a destructive species, might just be a synonym for A. lineatus. According to Staudacher et al (2011a), PCR analyses showed a high similarity between A. lineatus and A. proximus. Additionally, both species were found to be attracted to the same pheromone composition (Tóth et al 2008, Vuts et al 2012.…”
Section: Distributionmentioning
confidence: 99%
“…1/2013 Furlan 1998, Furlan 2004, ecology (Staudacher et al 2011a, Brunner et al 2011, crop preferences (Furlan 2011, Ritter unpublished data) and damage level (Furlan 2011). Furlan (2005b) divided Agriotes species into two groups, according to their life cycle: (1) species with adults overwintering, and (2) species with adults which do not overwinter.…”
Section: Population Monitoring and Damage Prediction Species Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…New monitoring approaches, including the assessment of adult populations using pheromones, are thus needed. The identification of wireworms to species level is a prerequisite to develop successful control measures, but it is challenging and represents an area where new techniques are needed to allow for reliable and rapid taxonomic assignment of larvae (Staudacher et al 2011). The search for effective biological control agents such as entomopathogenic fungi is another important aspect to develop new measures for wireworm regulation.…”
mentioning
confidence: 99%